(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2024)
Background. The article analyzes the role of the social pedagogue as a mediator in the establishment of a safe educational environment. It is noted that war and the general situation of a state of emergency significantly impact the educational environment in general secondary education institutions. Methods. Search of the available methodical and scientific literature with analysis of the found material, classification, systematization, generalization, comparison. Results. An analysis of the implementation of school mediation practices in German education demonstrates that it is based on both psychological and pedagogical achievements (the ideas of P. Natorp and the concept of Haltung) and normative and legal documents (minimum standards in certain federal states and recommendations of the Bundesverband Mediation). It has been established that in practice, various models of school mediation exist in German schools, which are classified according to who conducts the mediation, in what type of school and in which classes it is carried out, as well as in what context. The most popular model in German schools is the "Conflict Leaders" model by Ortrud Hagedorn, the essence of which is the confidential assistance of mediators in preventing and resolving conflict situations. Four advantages of the aforementioned model have been identified: the reduction of emotional tension, the accountability of the parties to the conflict, discussion, and balance. Сonclusions. The implementation of mediation in German education is also accompanied by a number of organizational problems (insufficient support from management, lack of systematic approach, ambiguity of goals) and content-related issues (confusion in defining functions and roles, focus on failures and shortcomings, uncritical belief in results, lack of transparency). Key aspects of the German mediation experience that need to be considered during its implementation in the Ukrainian educational space have been highlighted.